2010
DOI: 10.1111/j.1600-9657.2009.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral traumatic granuloma: report of a case and review of literature

Abstract: –  Traumatic granuloma is an uncommon condition considered to be a benign, reactive lesion that usually affects the tongue. The exact pathogenesis implicated in the development of this lesion is not clear. However, trauma has been found to be a contributing factor in a majority of the cases. Clinically, it often presents as an ulceration or an indurated submucosal mass. Microscopically, it is characterized by a diffuse polymorphic cell infiltrate composed predominantly of eosinophils extending deep into the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…In experimental studies, repeated injuries to the tongue in rats demonstrate similar lesions 4. Others have suggested that trauma is only a contributing factor in the development of EUOM and could facilitate the entry of unidentified aetiological factors such as microorganisms, toxins or foreign proteins into the underlying tissue to cause an inflammatory response 1 2 4. On the other hand, trauma is identified in less than 50% of cases 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In experimental studies, repeated injuries to the tongue in rats demonstrate similar lesions 4. Others have suggested that trauma is only a contributing factor in the development of EUOM and could facilitate the entry of unidentified aetiological factors such as microorganisms, toxins or foreign proteins into the underlying tissue to cause an inflammatory response 1 2 4. On the other hand, trauma is identified in less than 50% of cases 1.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the rapid growth, ulcerative nature and indurated borders of the usually single lesion, this condition can mimic SCC 1 2 6. In our patient, the clinical feature was so similar to SCC that the ENT specialist talked to the patient and her family about the necessity of hemiglosectomy and ipsilateral lymph node dissection after confirming the diagnosis by pathology.…”
Section: Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually unifocal, though multi-focal lesions and recurrences will be there occasionally. Both the sexes are equally affected and common in infant's .RFD is mostly associated with the eruption of primary lower incisor in older infants or natal teeth and neonatal teeth in newborns 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Natal teeth are not common; the prevalence ranges from one in 2000 to 1 in 3000 live births and are commonly lower central incisors [4] it occurs in babies less than two years of age. Commonly ulcer is present on the tongue (60% of the lesions), but other areas such as lip, palate, gingiva, vestibular mucosa and floor of the mouth may be the ulcer site [5]. It is a benign mucosal ulcer [6].…”
Section: Introductionmentioning
confidence: 99%